2007
DOI: 10.1200/jco.2007.11.8166
|View full text |Cite
|
Sign up to set email alerts
|

High Interleukin-15 Expression Characterizes Childhood Acute Lymphoblastic Leukemia With Involvement of the CNS

Abstract: Quantification of leukemic IL-15 expression at diagnosis predicts CNS status and could be a new tool to further tailor CNS-directed therapy in childhood ALL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
62
2
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 34 publications
4
62
2
2
Order By: Relevance
“…It has been shown that high expression of IL-15 correlates with CNS disease in pediatric ALL. 10 However, we found that IL-15 does not correlate in our series of adult patients with BCR-ABL negative ALL. These results may be in conjunction with multifunctional signals mediated by IL-15 and its unusual pattern of expression and secretion.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…It has been shown that high expression of IL-15 correlates with CNS disease in pediatric ALL. 10 However, we found that IL-15 does not correlate in our series of adult patients with BCR-ABL negative ALL. These results may be in conjunction with multifunctional signals mediated by IL-15 and its unusual pattern of expression and secretion.…”
Section: Discussioncontrasting
confidence: 60%
“…8,9 Recently, the powerful antiapoptotic properties of IL-15 have been suggested to confer a selective growth advantage to neoplastic cells promoting tumor cell growth, expansion, and organ infiltration of malignancies. 3,[7][8][9][10] Concerning the clinical relevance of IL-15 in hematopoietic malignancies, elevated IL-15 levels have been shown to affect the initial response to therapy and were associated with malignant transformation, including organ infiltration and disease progression, such as relapse. 3,[10][11][12][13] In adult ALL, clinical studies have defined immunophenotype and molecular genetic markers, as well as the duration of first remission, as the most significant independent prognostic determinants.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A high expression of IL-15 correlates with CNS disease in childhood ALL 55,56 and neurocognitive impairment. 57 Moreover, several IL-15 single nucleotide polymorphisms (SNPs) have been associated with minimal residual disease; 58 five SNPs (rs10519612, rs10519613, rs35964658, rs17007695, and rs17015014) located in the IL-15 locus were associated with childhood ALL treatment response.…”
Section: Allmentioning
confidence: 99%
“…These facts suggest that IL-15 may act as a cancer development stimulator in leukemia and lymphomas originating from B cell, T cell and NK cell. Observations such as activated of expression of IL-15 and IL-15R alfa by viral Tax protein in HTLV 1 associated T cell leukemia/lymphoma as well as association of IL-15 expression with mediastinal lymphadenopathy in acute lymphoblastic leukemia (ALL) and poor prognosis and inferior 5 year survival in B cell type ALL and higher risk of CNS relapse in pediatric ALL further supports that IL-15 may act as a cancer development cytokine in hematological malignancies originating from lymphoid cell lines [146,147]. However, observations in solid tumor and cancer cell lines did not show any direct effect of IL-15.…”
Section: Other Interleukinsmentioning
confidence: 82%